Genetic Diversity in Local Chow-Chow (Sechium edule Sw.) Germplasm of Sikkim - Kapoor, C.; Kumar, A.; Pattanayak, A.; Gopi, R.; Kalita, H.; Avasthe, R.K.; Bihani, S. (Indian Journal of Hill Farming, 2015)
Sixteen chow-chow accessions collected from different locations of Sikkim were studied for fifteen morphological and biochemical characters. Highest fruit weight was recorded in entry S8 (461g) followed by S9 (416g) and S1 (399.09g). Highest dry matter content was found in the entry S5. Entries S2, S3, S10 and S11 contained higher ascorbic acid content in their fruits. Twelve polymorphic RAPD markers were used for differentiating the 16 accessions, generated a total of 25 bands (2 bands per primer). The UPGMA dendrogram obtained from the cluster analysis using Jaccard’s similarity coefficient divided the accessions into four clusters. The morphological or biochemical characters of the accessions did not show association with the RAPD data.